Cross-cultural Adaptation and Validation of the International Knee Documentation Committee Subjective Knee Form in Filipino - Angel Luis Veloso; Edsel Arandia (Philippine Journal of Orthopaedics, 2024)
Objectives. The primary objectives of this study were to perform cross-cultural adaptation and to determine the validity and reliability of the Filipino IKDC Subjective Knee Form. Methodology. The IKDC subjective knee form was translated and cross-culturally adapted to Filipino. The process consisted of a forward translation, backward translation, review of versions by an expert committee, modification of the Draft Filipino version, and pre-testing of the Initial Filipino version. The clinimetric properties of the final Filipino IKDC subjective form, namely face and content validity, construct validity, internal consistency and test-retest reliability were measured from 101 respondents. Face and Content validity were explored with questionnaires, internal consistency was assessed with Cronbach Alpha, test-retest reliability was measured with interclass correlation coefficients, and construct validity was analyzed by comparing scores between respondents with injured knees with respondents with healthy knees. Results. The Filipino version of the IKDC subjective form has internally good clinimetric properties. Content validity showed that all items of the Filipino Version of the IKDC subjective form were perceived to be highly relevant by experts. Face validity showed that the participants graded the questionnaire items as easy to understand and relevant to their condition. Internal consistency, test-retest reliability and were interpreted as excellent and acceptable, with an ICC value of 0.99 and Cronbach’s Alpha of 0.702, respectively. Conclusion. The Filipino IKDC subjective knee form has good face validity, content validity and is a reliable patient reported outcome measure for knee function.